Metabolic versatility of acetogens in syngas fermentation: responding to varying CO availability - Moreira, João Paulo Carvalho (2025)
Syngas fermentation using acetogenic bacteria offers a promising route for sustainable chemical production. However, gasliquid mass transfer limitations and efficient co-utilization of CO and H2 pose significant challenges. This study investigated the kinetics of syngas conversion to acetate by Acetobacterium wieringae and Clostridium species in batch conditions under varying initial CO partial pressures (19 110kPa) in batch cultures. A. wieringae strains, exhibited superior growth in all gas compositions, with a maximum growth rate of 0.104h1. The distinct CO, H2, and CO2 consumption patterns revealed metabolic flexibility and adaptation to varying syngas compositions. Notably, A. wieringae strains and C. autoethanogenum achieved complete CO and H2 conversion, with C. autoethanogenum also exhibiting net CO2 uptake. These findings provide valuable insights into the distinct metabolic capabilities of these acetogens and contribute to the development of efficient and sustainable syngas fermentation processes.